RANCANG BANGUN MONITORING DAN PENYIMPANAN NILAI DAYA LISTRIK SECARA REAL TIME PADA BASIS DATA - Bayu Wiranatha, I Dewa Gde; Indra Partha, Cok Gede; Setiawan, Widyadi (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i01.p20, 2018)
Hotel management to monitor the energy to know the electrical energy consumption at the hotel. Energy monitoring is carried out in order to achieve the efficient use of electrical energy, for accurate energy monitoring requires a tool that can monitor the power consumption in real time and store on digital media or database so easy to access. Data stored on the database using the help of microcontroller and Ethernet Shiled connected to the LAN network. The sensors used in this research are voltage down 220VAC: 9VAC and current sensors with maximum current capacity of 100 A. The result of data recording is the highest current sensor deviation of 2.4% and the highest voltage sensor deviation is 0.4%.